Lipid nanoparticle-based mRNA vaccines in cancers: Current advances and future prospects - Huang, Tao; Peng, Lushan; Han, Yingying; Wang, Dan; He, Xiaoyun; Wang, Junpu; Ou, Chunlin (Frontiers in Immunology, 2022)
Messenger RNA (mRNA) vaccines constitute an emerging therapeutic method with the advantages of high safety and efficiency as well as easy synthesis; thus, they have been widely used in various human diseases, especially in malignant cancers. However, the mRNA vaccine technology has some limitations, such as instability and low transitive efficiency in vivo, which greatly restrict its application. The development of nanotechnology in the biomedical field offers new strategies and prospects for the early diagnosis and treatment of human cancers. Recent studies have demonstrated that Lipid nanoparticle (LNP)-based mRNA vaccines can address the poor preservation and targeted inaccuracy of mRNA vaccines. As an emerging cancer therapy, mRNA vaccines potentially have broad future applications. Unlike other treatments, cancer mRNA vaccines provide specific, safe, and tolerable treatments. Preclinical studies have used personalized vaccines to demonstrate the anti-tumor effect of mRNA vaccines in the treatment of various solid tumors, including colorectal and lung cancer, using these in a new era of therapeutic cancer vaccines. In this review, we have summarized the latest applications and progress of LNP-based mRNA vaccines in cancers, and discussed the prospects and limitations of these fields, thereby providing novel strategies for the targeted therapy of cancers.